Entropy analysis of thermo-solutal stratification of nanofluid flow containing gyrotactic microorganisms over an inclined radiative stretching cylinder. (1st September 2022) - Mandal, S.; Shit, G.C.; Shaw, S.; Makinde, O.D.
Abstract: Background and objective: Biomolecules of microorganisms are of greater importance in the industrial microbiology because, biosurfactants and surface-active molecules are produced by micro-organisms. Biosurfactants are used in the fields of enhanced oil recovery and various environmental bioremediation. The combined influence of nanofluids and microorganisms has various utilizations in industry such as micro-fluidics appliances including micro-channels and micro-reactors. We investigate the entropy generation of magnetohydrodynamic bioconvective flow of Maxwell nanofluid consisting of gyrotactic microorganisms over a radiative inclined stretching cylinder. The investigation reviews the notable characteristics of thermal radiation, Brownian motion of nanoparticles, thermophoresis effects, and chemical reactions. The novelty of the present work lies in the consideration of motile microorganisms with nanofluid, effect of curvature and the angle of inclination of the stretching cylinder on the flow and entropy generation. Methods: The nonlinear partial differential equations governing the nanofluid flow with bioconvection are transformed into ordinary differential equations using self-similar transformations. The numerical investigation uses a well-known shooting method with the Runge–Kutta–Fehlberg integration technique to solve the reduced system of equations. We have validated the computational results with existing literature. Results: It turns out that the concentration of nanoparticles intensified by regulating the Brownian motion and chemical reaction parameters. In contrast, the entropy generation through the Bejan number profiles has a controlling effect on the curvature of the cylinder, convective heat transfer coefficient, Brinkman number and Brownian motion parameter. Furthermore, it shows that the density and swimming speed of the motile organisms are strongly responsible for the enhancement of the entropy generation. Thus, the study bears the potential applications in variety of industrial microbiology. Highlights: Entropy generation of nano-fluid with gyrotactic microorganisms is investigated. Effect of bioconvection over a radiative inclined stretching cylinder is examined. Motile concentration has an enhancing effect on the curvature of the cylinder. Thermal irreversibility largely depend on bioconvection, thermal radiation and magnetic field. The study has important applications in the industrial microbiology including oil recovery.